Crowdsourcing in health professions education: What radiography educators can learn from other disciplines. Issue 2 (May 2019) - St John-Matthews, J.; Newton, P.M.; Grant, A.J.; Robinson, L.
Abstract: Objectives: Crowdsourcing works through an institution outsourcing a function normally performed by an employee or group of individuals. Within a crowdsource users, known as the crowd, form a community who voluntarily undertake a task which involves the pooling of knowledge resources. A literature review was undertaken to identify how the tool is being used in health professions education, and potential for use in radiography education. Key Findings: 17 papers were returned. Literature identified was assessed against an established crowdsourcing definition. Reviewing these yielded four themes for discussion: student selection procedures, lesson planning, teaching materials and assessment. Conclusion: Crowdsourcing is associated with innovative activities through collective solution seeking via a large network of users. It is increasingly being adopted in healthcare training and maybe transferable to educational activities within the field of radiography education. Highlights: Crowdsourcing is the outsourcing of a function performed by a group of individuals. Crowdsourcing is increasingly being adopted in health professions education. The most popular application was the assessment of simulated practical assessments. Other uses were instructional information design, course material, programme entry selection. These examples maybe transferable to radiography educational activities.